2018
DOI: 10.1111/pedi.12684
|View full text |Cite
|
Sign up to set email alerts
|

A single exercise session increases insulin sensitivity in normal weight and overweight/obese adolescents

Abstract: We measured the effect of an aerobic exercise session on postprandial glucose control in adolescents with habitually low-physical activity. The goal was to determine if the acute or residual response of exercise was altered in people who are overweight/obese (OW/Ob). Eleven normal weight, body mass index (NW, BMI = 48 ± 13 percentile) and 12 OW/Ob (BMI = 91 ± 5 percentile) participants completed 3 trials. In the no exercise (No Ex) trial, participants rested quietly before and after consuming a test meal. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…Unsurprisingly, the characteristics relating to body composition were more favourable in the high-fit group compared to the low-fit group (Table 1). A recent study supports these findings by showing that adolescents considered overweight/obese had a higher postprandial insulinaemic response by ~ 36% (Short et al, 2018). However, V̇O 2 peak in the aforementioned study (Short et al, 2018) was normalised to lean body mass, rather than total body mass, which makes comparisons with the characteristics in the current study difficult.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Unsurprisingly, the characteristics relating to body composition were more favourable in the high-fit group compared to the low-fit group (Table 1). A recent study supports these findings by showing that adolescents considered overweight/obese had a higher postprandial insulinaemic response by ~ 36% (Short et al, 2018). However, V̇O 2 peak in the aforementioned study (Short et al, 2018) was normalised to lean body mass, rather than total body mass, which makes comparisons with the characteristics in the current study difficult.…”
Section: Discussionsupporting
confidence: 48%
“…Despite this, it is unknown if the physical fitness of participants moderates the acute metabolic responses to exercise and whether there are any overall associations of fitness with postprandial insulinaemia and glycaemia. It has been suggested that those considered lower fit will see greater metabolic improvements from acute exercise than their higher fit counterparts (Cockcroft et al, 2015;Short et al, 2018Short et al, , 2013. On the other hand, it has also been suggested that those with a higher physical fitness will benefit more, by virtue of the ability to work at a higher absolute exercise intensity (Dring et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…Out of all the explanatory variables, waist circumference provided the strongest individual explanation of the variance in the postprandial insulinaemic response and was also a strong predictor in the final model. These data are supported by a group comparison of postprandial insulinaemia whereby overweight/ obese adolescents (aged 14-15 years) had a greater insulin AUC compared with normal-weight adolescents (22) , as well as supporting the relationship between adiposity and insulin sensitivity over a 2-year period in children (aged 9-11 years) (39) . Whilst previous research has identified differences in postprandial insulinaemia between young people considered overweight and normal weight, the present study offers novel insights into the relationship of adiposity on postprandial responses in adolescents.…”
Section: Discussionmentioning
confidence: 56%
“…Adiposity is a well-known risk factor for the development of insulin resistance and type 2 diabetes (2,9,10) , but there is very little known about how adiposity affects postprandial responses in adolescents. A direct comparison of overweight/obese and normal-weight adolescents, using BMI, found that those who were overweight/obese had a larger insulinaemic response to a standardised meal (22) . This study, however, only considered BMI as a proxy of adiposity and did not consider the measure of waist circumference which is the preferred measure of adiposity when considering CVD risk (23) .…”
mentioning
confidence: 99%
“…All participants and parents or guardians of those less than 18 years old provided informed consent in accordance with the University of Oklahoma Health Sciences Center Institutional Review Board, which approved the study. Physiological tests were conducted as previously described . Serum nonesterified fatty acid (NEFA) and triglyceride levels were measured by using enzymatic colorimetric assays (Wako Chemicals, Richmond, Virginia).…”
Section: Methodsmentioning
confidence: 99%